2009
DOI: 10.1007/s12149-009-0259-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of subareolar injection lymphoscintigraphy with the 1-day and the 2-day protocols for the detection of sentinel lymph nodes in patients with breast cancer

Abstract: The results of the identification of the sentinel node by subareolar injection according to 1-day or 2-day protocol, in breast cancer patients, showed no significant differences. Because the 2-day protocol allows for an adequate amount of time to perform the lymphoscintigraphy, it is a more useful protocol for the identification of sentinel nodes in patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
6
0
3
Order By: Relevance
“…The activity of 99m Tc-labelled nanocolloid used in our patients was not small compared with the common trend in the literature (Koizumi et al, 2003;Gutman et al, 2006;Wang et al, 2007;van Esser et al, 2009;Seok et al, 2009). We used 50 MBq (±10%) for same-day and 110 MBq (±10%) for 2-day procedures.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The activity of 99m Tc-labelled nanocolloid used in our patients was not small compared with the common trend in the literature (Koizumi et al, 2003;Gutman et al, 2006;Wang et al, 2007;van Esser et al, 2009;Seok et al, 2009). We used 50 MBq (±10%) for same-day and 110 MBq (±10%) for 2-day procedures.…”
Section: Discussionmentioning
confidence: 94%
“…We used 50 MBq (±10%) for same-day and 110 MBq (±10%) for 2-day procedures. Very different activities, from 7AE4 to 120 MBq for same-day procedures and from 37 to 370 MBq for 2-day procedures, have been reported (Koizumi et al, 2003;Gutman et al, 2006;Wang et al, 2007;van Esser et al, 2009;Seok et al, 2009). Few studies studied the influence on malignant node identification in relation to activity amount.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple other studies have also confirmed the efficacy of having injection day before surgery date. [14][15][16] The role of SPECT/CT imaging in LSG is limited as planar imaging is usually sufficient. SPECT/CT may help to improve the sensitivity of SLN detection, allow for more precise anatomical localisation and surgical approach for SLNB, especially in patients with unusual lymphatic drainage.…”
Section: Discussionmentioning
confidence: 99%
“…(INCA, 2009), (SAMPHAO et al, 2008) A média de idade dos nossos pacientes foi de aproximadamente 54 anos, o que é similar ao descrito na literatura, a qual evidencia a ocorrência de CA de mama em populações mais maduras, com média de idade variando entre 47 e 56 anos. (SEOK et al, 2010), (NALASHIMAN et al, 2010), (NOGUCHI et al, 2010), (SEOK et al, 2009) Segundo o INCA (2009) a idade continua sendo um dos principais fatores de risco do CA de mama. As taxas de incidência aumentam rapidamente até os 50 anos e posteriormente, este aumento ocorre lentamente.…”
Section: Características Clínicas E Demográficasunclassified
“…Estes valores estão de acordo com a literatura, que evidencia em ordem decrescente de freqüência o CDI, seguido pelo CDIS, CLI e, então, os demais tipos histológicos. (SEOK et al, 2010), (NALASHIMAN et al, 2010), (NOGUCHI et al, 2010), (SEOK et al, 2009), (ABDOLLAHI et al, 2009) Quanto ao grau histológico do tumor presente nos pacientes submetidos ao estudo, de acordo com a classificação de Scarff-Bloom-Richardson modificado por Elston-Ellis, a maioria apresentou grau II (48,6%), seguido do grau I e grau III com 25,7% cada. Na literatura o grau histológico é variável e depende do tipo de estudo abordado.…”
Section: Características Clínicas E Demográficasunclassified